Comparison of midazolam versus clonazepam as premedication scheduled for elective abdominal hysterectomies - Neeru Bala; Hardip Singh; Joginder Pal Attri; Lipsy Bansal; Sukhman Kaur (International Journal of Medical Research and Review, 2016)
Background and aim: Anxiety is one of the most common problem which affect the patient during surgical procedures. Thus, anxiolytics have a primary role as premedication preoperatively. With this background, we designed this study to compare anxiolytic effects of oral midazolam and oral clonazepam.Methods: Study was carried out in 80 patients scheduled for elective Abdominal hysterectomy and were divided into group of 40 each. Group M 40 patients were given Tab Midazolam 10 mg, 45 min before surgery. Group C of 40 patients were given Tab Clonazepam 2 mg, 45 min before surgery with a sip of water. All hemodynamic parameters, sedation score, satisfactory score, Hamitlon Anxiety Rating Scale were noted. The patient characteristics were analysed using “Chi-square test” and inter group comparison of the parametric data was done using the “unpaired t-test using software IBM SPSS 17.0.Results: Clonazepam is better anxiolytic than midazolam and has longer duration of anxiolytic effects and with minimal side effects and better hemodynamic stability than midazolam.Conclusion: Tab Clonazepam can be used as premedication to allay anxiety in the patients undergoing elective surgeries.